2016
DOI: 10.3139/113.110467
|View full text |Cite
|
Sign up to set email alerts
|

Micelle Formation of Morpholinium Bromide Surfactants in Aqueous Solution

Abstract: The micelle formation of N-alkyl-N-methylmorpholinium bromide (CnMMB, n = 12, 14, 16) surfactants in aqueous solution has been investigated. Their critical micelle concentration (CMC), effectiveness and efficiency of the surface tension reduction, and the maximum surface excess concentration were derived from the surface tension curves. Thermodynamic parameters were then evaluated in the temperature range of 25 °C ∼ 45 °C. The results showed that with increasing the alkyl chain length, the CMC values were decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…In the case of [Mor 1,12 ][Br], the decrease in surface activity is because of an increase in hydrophilic interaction because of the presence of extra electronegative element oxygen ‘O’ in the heterocyclic ring which makes it more hydrophilic. So because of the increase in hydrophilic interactions micellization tendency decreases and CMC values increase [ 24 ]. Also, from the thermodynamic parameters of micellization ( Table 2 ), this can be suggested that the micellization processes for both [C 12 mim][Br] and [Mor 1,12 ][Br] are mainly entropy-driven, and enthalpy contributions are very small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of [Mor 1,12 ][Br], the decrease in surface activity is because of an increase in hydrophilic interaction because of the presence of extra electronegative element oxygen ‘O’ in the heterocyclic ring which makes it more hydrophilic. So because of the increase in hydrophilic interactions micellization tendency decreases and CMC values increase [ 24 ]. Also, from the thermodynamic parameters of micellization ( Table 2 ), this can be suggested that the micellization processes for both [C 12 mim][Br] and [Mor 1,12 ][Br] are mainly entropy-driven, and enthalpy contributions are very small.…”
Section: Resultsmentioning
confidence: 99%
“…ILs comprising of longer alkyl chains are analogous to conventional surfactants which form aggregates in an aqueous medium [ 8 , 19 ]. Nitrogen-containing surfactants (i.e., N-heterocycles) including imidazolium, pyrrolidinium, pyridinium, piperidinium, morpholinium, and piperazidinium based ILs, have been investigated by several researchers owing to their unique structures and exceptional surface properties, which makes them different from the traditional ionic surfactants and hence, their aggregation behavior have been investigated in an aqueous medium [ 15 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. These aggregates are being widely studied not only because of their fundamental importance but also for their practical applications in numerous fields such as the synthesis of nanoparticles, microemulsions, organic or bio-organic molecules, etc [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…В литературе представлено большое количество работ, посвященных исследованию ПАВ с морфолиниевой головной группой [4][5][6][7][8][9][10][11][12][13]. Известно их использование в качестве стабилизаторов наночастиц [4], солюбилизирующих [5][6] и антимикробных агентов [7], катализаторов разложения фосфорорганических экотоксикантов [5,[8][9].…”
Section: супрамолекулярные системы на основе катионных пав: влияние пunclassified
“…Авторами работы [11] исследованы ПАВ с морфолиниевой головной группой и различной длиной углеводородного радикала (n = 12,14,16) (рис. 1, б).…”
Section: супрамолекулярные системы на основе катионных пав: влияние пunclassified